2014
DOI: 10.1016/j.cub.2014.08.066
|View full text |Cite
|
Sign up to set email alerts
|

GMF Promotes Leading-Edge Dynamics and Collective Cell Migration In Vivo

Abstract: SUMMARY Lamellipodia are dynamic actin-rich cellular extensions, which drive advancement of the leading edge during cell migration [1–3]. Lamellipodia undergo periodic extension/retraction cycles [4–8], but the molecular mechanisms underlying these dynamics and their role in cell migration have remained obscure. We show that gliamaturation factor (GMF), which is an Arp2/3 complex inhibitor and actin filament debranching factor [9, 10], regulates lamellipodial protrusion dynamics in living cells. In cultured S2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…Glia maturation factor-γ (GMF-γ) is a 17 kDa member of the ADF/cofilin family that is capable of inducing actin depolymerization and debranching [28]. GMF-γ is able to bind to the Arp2/3 complex at the junction of mother filaments and daughter filaments, which induces debranching of the actin meshwork [28, 29]. Subsequently, debranched filaments are severed by gelsolin and depolymerized by ADF/cofilin, which eventually generate more G-actin pools for subsequent rounds of actin filament polymerization and branching [4, 28, 29].…”
Section: Roles Of Dynamic Actin Cytoskeleton and Actin-associated Promentioning
confidence: 99%
“…Glia maturation factor-γ (GMF-γ) is a 17 kDa member of the ADF/cofilin family that is capable of inducing actin depolymerization and debranching [28]. GMF-γ is able to bind to the Arp2/3 complex at the junction of mother filaments and daughter filaments, which induces debranching of the actin meshwork [28, 29]. Subsequently, debranched filaments are severed by gelsolin and depolymerized by ADF/cofilin, which eventually generate more G-actin pools for subsequent rounds of actin filament polymerization and branching [4, 28, 29].…”
Section: Roles Of Dynamic Actin Cytoskeleton and Actin-associated Promentioning
confidence: 99%
“…However, although cofilin debranching activity has been studied and does occur, another cofilin-like molecule termed glia maturation factor (GMF, of which there are different isoforms) appears to be more specific for the Arp2/3 complex branches and is more efficient than cofilin in mediating debranching (Haynes et al, 2015;Poukkula et al, 2014;Ydenberg et al, 2013).…”
Section: Biochemistry Actin Treadmilling and Expression Of Cofilins mentioning
confidence: 99%
“…However, rather than binding to actin like ADF/cofilin, GMF binds directly to Arp2/3 complex via interactions with the Arp2 and p40/ARPC1 subunits [1214]. Through these interactions, GMF inhibits actin nucleation by Arp2/3 complex, and catalyzes the dissociation of daughter filaments from mother filaments, i.e., debranching [13, 32, 33]. A co-crystal structure of GMF-bound Arp2/3 complex revealed that one of the GMF binding sites to be located on the Arp2 and ARPC1/p40 subunits [14].…”
Section: Introductionmentioning
confidence: 99%